2008
DOI: 10.1017/s1751731108002930
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approach of gossypol-induced reproductive toxicity in male rabbits. Changes in seminal plasma amino acids and fatty acids

Abstract: This study was done to evaluate the effects of two sublethal doses of gossypol (4 and 20 mg/kg of BW, every other day) on some amino and fatty acid concentrations in male rabbit seminal plasma. Rabbits were chosen as an experimental animal owing to the fact that they are excellent model for reproductive toxicological effects. The experiment lasted 16 weeks and included two periods: a treatment period (first 8 weeks) where the animals were given the tested product, and a recovery period (second 8 weeks) where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
2
3
0
Order By: Relevance
“…Annexin 5 (32 kDa) was found to be one of the most abundant seminal plasma proteins in rabbit, which agrees with previous works (Taha et al. ; Arruda‐Alencar et al. ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Annexin 5 (32 kDa) was found to be one of the most abundant seminal plasma proteins in rabbit, which agrees with previous works (Taha et al. ; Arruda‐Alencar et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Annexin 5 (32 kDa) was found to be one of the most abundant seminal plasma proteins in rabbit, which agrees with previous works (Taha et al 2011;Arruda-Alencar et al 2012). This protein is an anticoagulant that appears to have a beneficial effect in maintaining rabbit sperm viability, given its positive correlation with several semen parameters such as sperm vigour, concentration and percentage of morphologically normal sperm (Arruda-Alencar et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Casares-Crespo et al (34) isolated a 19 kDa protein band, corresponding to the lipocalin allergen Ory c 4 precursor, from seminal plasma of rabbits, which was suggested to be related to improved fertility. Additionally, Taha et al (35) found a positive association between the seminal plasma level of the 21.5 kDa protein band and sperm membrane integrity and intact acrosomes. Furthermore, the 30 kDa protein band is closely related to a family of proteins called binder sperm proteins (BSPs) in the seminal plasma of many mammals, including rabbits, rats, bulls, goats, and rams (36,37).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, this discussion focuses on some free amino acids of interest and offers some insight into their possible biological effect and their possible imbalance resulting from GOS administration. Taha et al, (2008) reported that GOS administration reduced rabbit seminal plasma concentrations of TAA, total EAA and total non-EAA in a dose-dependent manner, and this was associated with poor-quality semen.…”
Section: Effect Of Level Of Gos On Amino Acids and Fatty Acidsmentioning
confidence: 98%
“…The endogenous respiration of spermatozoa depends largely on oxidation of the hydrolysed acyl groups of plasmalogens (Hartree and Mann, 1961); endogenous fatty acids may also be utilised and are readily incorporated into the lipid of spermatozoa (Mills and Scott, 1969). Taha et al (2008) reported that rabbit GOS administration caused decreases in total USFA and increases in SFA and SFA/USFA ratio in a dose-dependent manner and was also associated with poor-quality semen. To our knowledge, no other studies dealing with the effect of GOS on blood plasma concentration of TFA are available.…”
Section: Effect Of Level Of Gos On Amino Acids and Fatty Acidsmentioning
confidence: 99%